2017
DOI: 10.2334/josnusd.16-0731
|View full text |Cite
|
Sign up to set email alerts
|

Influences of differences in tray design and impression material on impression pressure at edentulous mandible

Abstract: The aim of this study was to examine the effects of tray design and impression material on impression pressure in a clinical simulation model of an edentulous mandible. Two types of polyvinylsiloxane elastomer, one type of polyether elastomer, and one type of alginate were used. The three tray types had no relief, 0.36 mm of relief, or 1.4 mm of relief, with or without escape holes. Impression pressure was measured at the median alveolar crest, the bilateral alveolar crests corresponding to molars, and the bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
1
1
Order By: Relevance
“…Sayumi et al [ 25 ] and Al-Ahmad et al [ 15 ] found that impression pressure was higher at the median alveolar crest than at the buccal shelf area in the tray without a spacer, but in our study, the result was found with more microstrain value in the buccal shelf area (953.03) than in the alveolar crest area (897.07). There may be several reasons why there is a difference in results between this study and that of Al-Ahmad et al and Sayumi et al The main difference between these studies is that our study was in vivo, and the pressure was applied manually with fingers at the first molar areas.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Sayumi et al [ 25 ] and Al-Ahmad et al [ 15 ] found that impression pressure was higher at the median alveolar crest than at the buccal shelf area in the tray without a spacer, but in our study, the result was found with more microstrain value in the buccal shelf area (953.03) than in the alveolar crest area (897.07). There may be several reasons why there is a difference in results between this study and that of Al-Ahmad et al and Sayumi et al The main difference between these studies is that our study was in vivo, and the pressure was applied manually with fingers at the first molar areas.…”
Section: Discussioncontrasting
confidence: 77%
“…Sayumi et al [ 25 ] found that impression pressure on buccal shelves in trays with 1.4 mm of relief and escape holes at the alveolar crests was significantly higher than that on the alveolar crests in all impression materials. He also claimed that increasing relief thickness expands the space through which impression material flows near the mandibular alveolar crests, thereby reducing impression pressure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case Inoue et al consider three types of impression materials, polyvinylsiloxane elastomer, polyether elastomer, and alginate (Figure 1, Figure 2 and Figure 3). The pressure during setting had no significant effect on precision, but an excessive pressure can be alleviated with escape holes and relief on the tray [43]. Hyde et al in 2014 recruited 85 patients and performed an Randomized Controlled Trial (RCT) using alginate or silicone impressions for complete denture creation.…”
Section: Discussionmentioning
confidence: 99%
“…De manera general nuestro estudio corrobora esta información, ya que en todos los grupos estudiados y el alginato cromático utilizado evidenció cambios dimensionales pequeños que oscilaron entre 0,06-0,97 mm; esto señala que antes de los 15 minutos de vaciados los cambios dimensionales son mínimos, pero no por eso se debe prolongar el tiempo de vaciado. Se ha aconsejado que las impresiones deben ser vaciadas antes de los 30 minutos porque existen cambios dimensionales que obligarán a repetir la impresión con alginato 22 . En nuestra investigación el alginato uti-lizado no evidenció amplios cambios dimensionales al cabo de 15 minutos de vaciado, pese a que otros autores como Iwasaki y cols.…”
Section: Discussionunclassified